Vegetative growth of rubber tree clones - Gonçalves, Paulo de Souza; Vasconcelos, Maria Elizabeth da C.; Silva, Edson B. da (Pesquisa Agropecuaria Brasileira, 2014)
The stem development and bark thickness of IAN 117, IAN 873 and Fx 3899 clones were evaluated. The experiments were developed in areas of Kaolinitic Yellow Latosol and coarse Yellow Latosol that occurs at the “Centro Nacional de Pesquisa de Seringueira", Manaus, Amazon state, Brazil. It was used a completely random design with 100 plants per plot with spacing 3 by 7 meters. The preliminary results in this experiment show that the clones do not show a defined pattern of variation with two and half years old.